(untitled) - Pellikaan, Huib (Cambridge, UK, 2002)
This book examines environmental policy-making through research into individuals' reaction to environmental issues. The authors argue that self-interest is just one of a number of motives which affect people's choices and that voluntary environmental polices are thus more likely to succeed than might be expected. Their arguments base on detailed surveys of public opinion
Keywords: Environmental policy,Environmental protection,Chính sách môi trường,Bảo vệ môi trường; Citizen participation; Netherlands,Netherlands,Hà Lan